DFT Studies on the Hyperpolarizabilities of Organometallic Complexes Containing Nitrile Thienyl Derived Ligands - Mendes, Paulo J. (2013)
The research of nonlinear optical (NLO) materials has grown in the past decades due to the potential application in optical device technology, like data storage, communication and bio-sensing. [1] For obtaining large molecular second-order nonlinear optical (SONLO) responses, i.e. large hyperpolarizabilities (β), molecules have to possess typical “push-pull” asymmetric structures. Organometallic complexes presenting heterocyclic organic chromophores have proven to be promising systems in this field. For instance, η5-monocyclopentadienylruthenium(II) and iron(II) complexes containing 1,2-di-(2-thienyl)-ethene and oligothiophene nitrile derived ligands have been studied for this purpose. [2-4] However additional studies using DFT were found to be very useful in order to understand the SONLO mechanism in these complexes. This work presents a Density Functional Theory (DFT) study on the optical properties and quadratic hyperpolarizabilities (β) of η5-monocyclopentadienyliron(II) and ruthenium(II) complexes containing the cited nitrile derived ligands as chromophores. An attempt to correlate the SONLO properties with the features of the calculated electronic structure and UV/Vis spectra of those complexes, in particular the lowest energy electronic transitions, will be performed. The elucidation of the most important electronic properties determining large β may guide the design of new molecules with interesting NLO properties.